Estimating the underground economy, illegal money and tax evasion in Qatar evidence from currency demand function - Awadh Ahmed Mohammed Gamal (Tanjong Malim, 2019)
Estimating the underground economy, illegal money and tax evasion in Qatar evidence from currency demand function by Awadh Ahmed Mohammed Gamal